Kuanggong Suxie - Budan, Bai (China, 2010)
The film director interviews miners, the invisible auxiliaries of Chinese society in the throes of change. Having their poor country lives, miners go hundreds of meters underground every day to mine coal. Their life and future is uncertain but they continue to search for hope in the realms of darkness. Datong, the mining capital of the Shanxi province.
Verzio Film Festival Submission
Keywords: Documentary films